2014
DOI: 10.3944/aott.2014.14.0098
|View full text |Cite
|
Sign up to set email alerts
|

Fixation of intertrochanteric femur fractures using Proximal Femoral Nail Antirotation (PFNA) in the lateral decubitus position without a traction table

Abstract: While the nailing of intertrochanteric fractures in a lateral decubitus position does not provide ideal quadrant placement and TAD, results are encouraging probably due to the excellent stability that is provided by PFNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 13 publications
0
11
0
1
Order By: Relevance
“…[22,23] Among the studies evaluating the results of centralcentral or inferior-central application of the helical blade, a few inferior-posterior application cases were specified, and cut-out was not observed in these cases as we hypothesized so. [24][25][26] Lee et al [27] performed an evaluation of the biomechanical effect of different blade positions on a simulated pertrochanteric fracture by means of a computed tomography-based three-dimensional finite element model. They revealed that inferior and posterior blade positions had the larger area of compressive strain at the fracture surface than other three positions.…”
Section: Discussionmentioning
confidence: 99%
“…[22,23] Among the studies evaluating the results of centralcentral or inferior-central application of the helical blade, a few inferior-posterior application cases were specified, and cut-out was not observed in these cases as we hypothesized so. [24][25][26] Lee et al [27] performed an evaluation of the biomechanical effect of different blade positions on a simulated pertrochanteric fracture by means of a computed tomography-based three-dimensional finite element model. They revealed that inferior and posterior blade positions had the larger area of compressive strain at the fracture surface than other three positions.…”
Section: Discussionmentioning
confidence: 99%
“…Modifiable risk factors for cut-outs are mainly the reduction position, obtaining Cal-TAD or TAD values, and avoiding an inappropriate position of the implant in terms of femoral head quadrants. Turgut et al [26] concluded that these three important criteria should be fulfilled while treating intertrochanteric fractures with the help of a proximal femoral nailing. In light of their studies, the cases were divided into eight scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…The feasibility of these operations without using the traction table has been reported in previous studies. Researchers who used the manual traction method with the lateral decubitus position due to the absence of a traction table in their centers reported that, this method did not completely obviate the tip-apex distance and ideal quadrant placement of the screw [10]. Şahin et al compared the patients who were operated with traction table with those manual traction applied in the supine position in unstable intertrochanteric femur fractures and no significant difference was observed between the groups when the surgical or postoperative parameters were evaluated [5].…”
Section: Discussionmentioning
confidence: 99%